A Rare Axonal Variant of Guillain-Barré Syndrome following Elective Spinal Surgery - Jessica R. Dowling; Thomas J. Dowling (Case Reports in Orthopedics)
Acute motor and sensory axonal neuropathy (AMSAN) is a rare axonal variant of Guillain-Barré syndrome. AMSAN is considered the most severe form of GBS, known for its rapid onset of severe symptoms, and often leading to quadriparesis within 7 days of initial symptom onset. We present a case of a middle-aged Caucasian female who developed AMSAN 2 weeks following an elective spinal surgery. Although rare, GBS has been reported as a complication of surgery. GBS classically presents as ascending motor weakness starting in the lower extremities following a gastrointestinal or upper respiratory tract infection. This patient’s GBS manifested slightly differently, with both sensory and motor symptoms of her thoracic region and lower extremities, with no preceding history indicative of infection. To the authors’ knowledge, this is the first reported case of AMSAN following spinal surgery. Because of its risk of significant morbidity and mortality, as well as similar presentation to more common spinal postoperative complications, GBS should always be included in the differential diagnosis whenever motor or sensory weakness is observed after spinal surgery.